Critical Analysis of Radiology Advances, Diagnostic Accuracy, And Ethical Considerations in Imaging - Alqarni, Mosa Salem; Omar, Hamza Ali Al; Assiri, Mubarak Ayed; Matiq, Saeed Ahmed; Al Jabbar, Abdullah Saeed; Al Jaber, Basem Ali; Alqahtani, Abdulmajeed Saleh; Alqahtani, Ali Saeed Ali; Asiri, Mohammed Hadi; Al Qasem, Muhannad Hassan (Journal of Ecohumanism, 2024)
This paper critically evaluates the current developments in radiology, the diagnostic accuracy of medical imaging, and the moral implications thereof. In this recent technology advancement era, especially in the field of imaging modalities, AI and machine learning, functional MRI, and PET scans are some of the additions that have added strength to the diagnostic capabilities in numerous medical specialties. At the same time, they pose several pressing ethical questions concerning data protection, the integration of AI into the decision-making process, and the availability of these tools in various facilities. This paper discusses the literature, the latest research findings, and recommendations for enhancing the diagnostic process and associated ethical dilemmas are provided in this paper.